2021
DOI: 10.2174/0929866527666200813202918
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Role of Aromatic Residues in the Antimicrobial Peptide BuCATHL4B

Abstract: Background: Antimicrobial Peptides (AMPs) are an attractive alternative to traditional small molecule antibiotics as AMPs typically target the bacterial cell membrane. A Trp-rich peptide sequence derived from water buffalo (Bubalus bubalis), buCATHL4B was previously identified as a broad-spectrum antimicrobial peptide. Objective: In this work, native Trp residues were replaced with other naturally occurring aromatic amino acids to begin to elucidate the importance of these residues on peptide activity. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…A large number of diverse temporins and aureins, secreted from the skin of several frog species, protect these amphibians from infections in the wild. In another example, short Trp-rich AMPs provide antimicrobial defense to the water buffalo ( Bubalus bubalis ) [ 96 ] and have been subjected to mutational analysis. An optimally designed variant, WRK-12 (WRLRWKTRWRLK), was shown to efficiently target LPS and bacteria-specific phospholipids on the membrane [ 97 ], and as with many other AMPs, the placement of the Trp residues on one face of the helix ( Figure 7 A) was crucial for amphiphilicity and membrane interaction.…”
Section: Interacting Partners Of Trp Residues In a Polypeptidementioning
confidence: 99%
“…A large number of diverse temporins and aureins, secreted from the skin of several frog species, protect these amphibians from infections in the wild. In another example, short Trp-rich AMPs provide antimicrobial defense to the water buffalo ( Bubalus bubalis ) [ 96 ] and have been subjected to mutational analysis. An optimally designed variant, WRK-12 (WRLRWKTRWRLK), was shown to efficiently target LPS and bacteria-specific phospholipids on the membrane [ 97 ], and as with many other AMPs, the placement of the Trp residues on one face of the helix ( Figure 7 A) was crucial for amphiphilicity and membrane interaction.…”
Section: Interacting Partners Of Trp Residues In a Polypeptidementioning
confidence: 99%
“…For example, Locock and coworkers have demonstrated that cationic methacrylate polymers penetrate the cell membrane of S. mutans and bind to DNA in the cytosol (Michl et al, 2020). Some AMPs were reported to target the intercellular components in bacteria including DNA (D'Souza et al, 2021;Le et al, 2017;Necelis et al, 2021). While these mechanisms are reported for specific AMPs, it is likely that any AMPs can simultaneously bind to different sites in bacteria including the cell wall, membrane, and intracellular proteins and DNA/RNA, and this promiscuous targeting may individually or collectively contribute to killing of bacteria (Mahlapuu et al, 2020).…”
Section: Mode Of Action and Cellular Targetsmentioning
confidence: 99%
“…According to the literature, tryptophan (W) has a higher membrane insertion tendency than the other 19 natural amino acids. Peptides containing tryptophan (W) and arginine (R), such as WRWRWR, VRRFPWWWPFLRR, , AIPWIWIWRLLRKG (BuCATHL4B), WWWLRRRW, and RRRWWWWV, are considered to have the most attractive properties suitable for antimicrobial agents. It has been reported that phenylalanine (F) acts as a membrane anchor in some AMPs .…”
Section: Introductionmentioning
confidence: 99%